Cytomegalovirus Antibody Responses Associated With Increased Risk of Tuberculosis Disease in Ugandan Adults. (5th November 2019) - Stockdale, Lisa; Nash, Stephen; Farmer, Ruth; Raynes, John; Mallikaarjun, Suresh; Newton, Robert; Fletcher, Helen A
Abstract: Background: Recent evidence highlights human cytomegalovirus (HCMV) and immune activation as risk factors for tuberculosis disease. It is not known whether other herpesviruses are also implicated, nor whether a dose-response relationship exists between tuberculosis risk and herpes coinfection. Methods: This nested case-control study used stored serum samples from 25 persons with tuberculosis up to 10 years before tuberculosis diagnosis and between 3 and 6 matched controls without tuberculosis from a rural Ugandan cohort. Samples were investigated for Epstein-Barr virus, herpes simplex virus, and HCMV-specific immunoglobulin G (IgG), serum markers of inflammation, and mycobacterial antibody levels. Results: Humoral response to HCMV, but not Epstein-Barr or herpes simplex virus, was associated with increased risk of active tuberculosis disease up to 10 years before diagnosis. Individuals with medium HCMV IgG were 2.8 times more likely to have tuberculosis ( P = .055), and those with high HCMV IgG 3.4 times more likely to have tuberculosis ( P = .007). Mycobacterial antibody levels were not associated with differences in odds of tuberculosis disease. Interferon-induced protein 10 was independently associated with increased odds of tuberculosis (odds ratio, 4.2; P = .009). Conclusions: These data provide evidence of a dose response between magnitude of HCMV IgG with risk of tuberculosis disease. An inflammatory environment, characterized by serum interferon-induced protein 10 and interleukin 1α, is independently associated with increased risk of tuberculosis disease. Abstract : A dose-dependent increased risk of tuberculosis disease was seen with increasing human cytomegalovirus exposure as measured by immunoglobulin G in this Ugandan cohort. Increased tuberculosis risk was also associated with an inflammatory profile of interferon-induced protein 10 and interleukin 1α.